Pengembangan E-Modul Writing For Professional Context Berstandar Cefr Berdasarkan Karakteristik Pekalongan Kota Kreatif Dunia - Inayatul Ulya; M. Fajru Sidqi (JURNAL LITBANG KOTA PEKALONGAN, 2020)
The development of technology demanded the teaching material to be designed digitally. This study was aimed to develop CEFR (Common European Framework) -standard Writing for Professional Context teaching material in the form of Pekalongan the world creative city e-module. Research and development (R &D) was used in conducting this research. Observasion sheet, questionnaire and interview were used to collect the data. The results showed that E-Model of Writing for professional context was needed by the students. Therefore, the researcher did a plan of developing an e-module. After it was designed, it was validated by the validators for getting the suggestion of the betterment. Finishing the validation process, next the e-module of Writing for Professional Context standardized by CEFR with the characteristic of Pekalongan the World Creative city was revised and published. The title of the e-modul is Let’s Write: Pekalongan the World Creative City. The texts types in this e-modul were written with their social functions, generic structure and linguistic. The content of the texts described Pekalongan as the World Creative City. Keywords: CEFR, e-module, writing, creative